Charter for the City and County of San Francisco: Proposed by the Board of Freeholders, Elected in Pursuance of the Provisions of Section 8, Article XI, of the Constitution of the State of California 31 (1883) - (:unkn) unknown (My University, 1883)
Article 2-Of the Legislative Department, Chapter 4-Of Legislative Powers, § 1, No. 13: Empowered the local supervisors to regulate the sale and use of guns, pistol, firearms. Prohibited the sale of any toy cannon, gun, pistol, or other toy weapon to any minor or children.
Keywords: TRANSFER; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES